(untitled) (Journal of Economic, Administrative and Legal Sciences, 2024)
After the establishment and completion of the rules of international humanitarian law, the thoughts and minds of researchers have become preoccupied with the effectiveness of those rules in limiting violations and crimes occurring during armed conflicts. Can the mechanisms provided for in international humanitarian law conventions play a role in the effectiveness of this law's provisions?Knowledge of the available mechanisms for the implementation of international humanitarian law is essential in today's time, especially in the light of variables and their weaknesses; to finding out the real reasons for the continuing violations, the implementation of international humanitarian law is a process that presupposes the existence of numerous mechanisms functioning in time of peace and war and even after the end of the conflict.Modern-day conflicts have revealed States' lack of respect for the provisions of international humanitarian law and the international humanitarian law has various mechanisms to ensure its implementation at the domestic and international levels, but the States engaged in armed conflict lack the political will and practical capacity to assume their obligations; has led to the inability of international humanitarian law to achieve its objectives.